The evolution of astronomy In Iraq during the Abbasid era (Journal of the College of Basic Education, 2023)
Astronomy was one of the most closely related sciences to the Islamic cultural and social reality. Rather, it gained a certain specificity thanks to its treatment of religious issues of concern to Muslims anywhere at that historical stage. We find that determining the direction of the Qiblah (Makkah Al-Mukarramah) from several different points on the surface of the earth and the classification of astronomical tables For the timing of prayer with all these local issues